2021
DOI: 10.11591/ijphs.v10i4.21023
|View full text |Cite
|
Sign up to set email alerts
|

What is factor contributing to medical student learning anxiety during COVID-19 pandemic? A systematic review

Abstract: Changes in education aspects increase the risks for mental and emotional disorders on students during the COVID-19 pandemic. This article aimed to discover the factors are contributing to medical students' learning anxiety during the COVID-19. A systematic review was written based on scientific article identification on three databases of Science Direct, PubMed NCBI, and EBSCO using terms of anxiety, factors, students, and COVID-19. The authors selected and analyzed using PRISMA based on predetermined inclusio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 53 publications
0
3
0
1
Order By: Relevance
“…In our study, lower rates of anxiety and stress were found in students who had experienced offline classes and had undergone the hybrid or blended learning method during the COVID-19 pandemic. A longer offline learning experience decreased the level of anxiety and stress among the medical students, as there were still more achievable clinical skills than those obtained with full online learning methods [ 55 , 56 ]. Our finding was also affected by the participants as our study sample was predominated by preclinical than clinical students, implying that preclinical students still did not understand the importance of offline classes compared with clinical students who require more offline clinical skill development rather than just discussing it online and will soon become professional medical health teams in the field [ 56 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…In our study, lower rates of anxiety and stress were found in students who had experienced offline classes and had undergone the hybrid or blended learning method during the COVID-19 pandemic. A longer offline learning experience decreased the level of anxiety and stress among the medical students, as there were still more achievable clinical skills than those obtained with full online learning methods [ 55 , 56 ]. Our finding was also affected by the participants as our study sample was predominated by preclinical than clinical students, implying that preclinical students still did not understand the importance of offline classes compared with clinical students who require more offline clinical skill development rather than just discussing it online and will soon become professional medical health teams in the field [ 56 58 ].…”
Section: Discussionmentioning
confidence: 99%
“…All the articles were sourced from highly reputable journals listed in the 1773 SCOPUS and Web of Science database. According to Budiman et al [37] and Sholihah et al [38], this study applied the preferred reporting items for systematic reviews and meta-analyzes (PRISMA) method. The keywords employed to search appropriate research articles in the SCOPUS and Web of Science database are "mental health", "lecturer", "professor" and "COVID-19".…”
Section: Research Methods 21 Data Sources and Search Strategymentioning
confidence: 99%
“…Systematic review oleh Budiman et al, (2021) menjelaskan terdapat 2 faktor yang memengaruhi tingkat kecemasan mahasiswa kedokteran di era pandemi, yaitu faktor internal dan faktor eksternal. Faktor internal didalamnya termasuk usia, jenis kelamin, dan kurangnya pengetahuan sedangkan faktor eksternal mencakup beban akademik yang berat dengan metode pembelajaran daring, pembatasan sosial berskala besar (PSBB)/lockdown, aktivitas fisik, dan perubahan status sosial ekonomi [8]. Dari aspek usia, responden penelitian termasuk dalam tahapan perkembangan adolescence/remaja sampai dengan young adulthood/dewasa awal.…”
Section: Pembahasanunclassified